2009
DOI: 10.1002/jcc.21238
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of the detoxification of paraoxon catalyzed by phosphotriesterase

Abstract: Combined QM(PM3)/MM molecular dynamics simulations together with QM(DFT)/MM optimizations for key configurations have been performed to elucidate the enzymatic catalysis mechanism on the detoxification of paraoxon by phosphotriesterase (PTE). In the simulations, the PM3 parameters for the phosphorous atom were re-optimized. The equilibrated configuration of the enzyme/substrate complex showed that paraoxon can strongly bind to the more solventexposed metal ion Zn β , but the free energy profile along the bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 108 publications
(106 reference statements)
1
64
0
Order By: Relevance
“…The biosensors inability to detect these ubiquitous phosphates is consistent with the reported class of PTE that catalyzes these pesticides at a much slower rate. 51,54,62 Additional pesticides that do not contain phenolic-leaving groups or are not catalyzed by PTE (dichlofenthion, fenitrothion, phoxim, and dimethoate) were also tested and do not show any substantial increase in oxidation current. Paraoxon was then added again to the solution, and a similar step height was observed demonstrating that the immobilized PTE was still active.…”
Section: −52mentioning
confidence: 99%
See 1 more Smart Citation
“…The biosensors inability to detect these ubiquitous phosphates is consistent with the reported class of PTE that catalyzes these pesticides at a much slower rate. 51,54,62 Additional pesticides that do not contain phenolic-leaving groups or are not catalyzed by PTE (dichlofenthion, fenitrothion, phoxim, and dimethoate) were also tested and do not show any substantial increase in oxidation current. Paraoxon was then added again to the solution, and a similar step height was observed demonstrating that the immobilized PTE was still active.…”
Section: −52mentioning
confidence: 99%
“…PTE degrades paraoxon by hydrolyzing the P−O bond yielding diethyl phosphate and p-nitrophenol, which has a strong absorption at 405 nm with an extinction coefficient of ∼18 000 M −1 cm −1 , opposed to paraoxon which has minimal absorption ( Figure 5a). 54 Similar to methods described, 55 three varying ratios of PTE ink (0.5, 1, and 5% which accounts for 2, 4, and 20 nM PTE) were assayed versus varying concentrations of paraoxon (1, 2, 4, and 8 μM). A standard enzymatic rate reaction model was constructed using Sigma plot's enzyme module ( Figure 5b).…”
Section: −52mentioning
confidence: 99%
“…Thus, taking B3LYP/6-31G(d,p) as the standard, PM6 fails to predict the correct mechanism for PTE, which also explains the very large errors observed for the PM6 single point calculations in Table 1. The PTE mechanism has been studied using AM1 (Wong and Gao, 2007), PM3 (Zhang et al, 2009), and AM1/d-based QM/MM methods (López-Canut et al, 2012) and that these studies have suggested other reaction mechanisms. We emphasize that we have not explored the mechanism of PTE using PM6 but simply compared the structures resulting from the PM6 geometry optimizations initiated from the B3LYP/6-31G(d,p) geometries obtained by Chen et al (2007) In summary, geometry optimization with PM6 shows that for PTE this method predicts a different mechanism compared to B3LYP/6-31G(d,p), consistent with the fact that PM6//B3LYP/6-31G(d,p) energetics differ very significantly from the reference values as discussed above.…”
Section: Effect Of Geometry Optimizationmentioning
confidence: 99%
“…[2] There were also many similar works dedicating to uncover the mechanism of enzymatic catalysis by means of molecular modeling and quantum theory. [3][4][5] However, in most of previous studies the key residues of enzyme and the substrates are traditionally partitioned from the whole protein-ligand complexes, and then treated as a small complex entity. Although this scheme has been successfully applied in some enzyme-substrate systems, there are several disadvantages that undermine the accuracy and reliability of the computations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yuanchao Li et al investigate the roles of anchor residues and water in the process of epitope peptides binding to HLA-A*0201 by using of QM/MM, [7] and Jans H. Alzate-Morales et al explored the binding modes and potency of the inhibitors between guanine derivatives and cyclin-dependent kinase 2(CDK2) by using QM/MM, [8] and there were also many similar works dedicating to uncover the mechanism of enzymatic catalysis by means of ONIOM. [3][4][5] In the present work, we employed ONIOM methodology and docking to explore the influence of individual amino acids of Bacillus subtilis (B.sub) lipase A on the hydrolysis reaction, with the aim to guide mutagenesis experiments on the basis of computationanl framework. After preliminary probing using PROBE program [29] a hydrophilic residue Ile12 which has intensive van der Waals contacts with the inhibitor in the complex system was selected as a hotspot.…”
Section: Introductionmentioning
confidence: 99%